Reporting on social exclusion: standard of living and social participation in Hungary, Spain, and Germany - Petra Böhnke (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2001)
The issue of social exclusion, currently of particular concern to policy makers in Brussels, is a manifestation of new aspects of social inequality that are supposed to go along with persistent high unemployment rates and increasing poverty affection. The concept provides a multidimensional and dynamic perspective of the resultant weakened possibilities to participate in social life. The growing acceptance of the term, however, has not been accompanied by a consensus regarding who exactly belong under its rubric nor how this could be verified empirically. This contribution makes an effort to cut down the broad meaning of social exclusion in order to propose dimensions and indicators for measurement and monitoring purposes. With the help of actual data from the Euromodule, a representative survey instrument for European welfare comparison, the interplay between standard of living and social participation is analysed in Hungary, Spain, and Germany. The three countries represent different European regions and varying types of welfare and social protection policies. Decisive factors influencing vulnerability to exclusion include relative perceptions of deprivation, the general level of welfare in a country as well as access to support from social networks. – – Prozesse sozialer Ausgrenzung spielen gegenwärtig im europäischen sozialpolitischen Diskurs eine bedeutende Rolle, betont werden neue Aspekte sozialer Ungleichheit, die man insbesondere mit anhaltender Langzeitarbeitslosigkeit und wachsender Armut in Verbindung bringt. Das Exklusionskonzept bietet einen mehrdimensionalen und dynamischen Zugang zur umfassenden Analyse gesellschaftlicher Teilhabe. Trotz der großen Akzeptanz der Ausgrenzungsterminologie steht ein Konsens über Definitionen und empirische Messung bislang aus. In diesem Beitrag werden Dimensionen und Indikatoren zur Messung und Dokumentation von Ausgrenzungsprozessen vorgeschlagen. Mit Hilfe von Euromodule-Daten, einer repräsentativen Bevölkerungsumfrage für europäische Wohlfahrtsvergleiche, wird das Zusammenspiel von materiellem Lebensstandard und sozialer Teilhabe in Ungarn, Spanien und Deutschland analysiert. Die drei Länder unterscheiden sich in ihren sozialen Sicherungssystemen ebenso wie in ihrem Wohlfahrtsniveau. Vergleichsprozesse und Unterstützung durch soziale Netzwerke sind zwei wichtige Faktoren, die das Risiko sozialer Ausgrenzung wesentlich beeinflussen.
Keywords: 300; Soziale Isolation; Lebensstandard; Sozialer Indikator; Vergleich; Ungarn; Spanien